IMPACT OF VISUOMOTOR BEHAVIOUR REHEARSAL ON PSYCHOMOTOR ABILITY AND SOCCER PERFORMANCE - NURFARAH EZZATY BINTI MOHD ZAHIR,; DR. ASOK KUMAR GHOSH,; DR. SOUMENDRA SAHA, (International Journal of Pharma and Bio Sciences, 2016)
The present study was conducted to extrapolate the obscure relationships between open and closed-skill activities in defining successful soccer performance. Cognitive-emotional mediators of motor skill transitions were attempted to be examined in eighty-five young male high performing soccer players, while they were engaged in adopting Visuomotor behavior rehearsal (VMBR) training. Evaluation of motor skills and abilities pertaining to bidirectional and bilateral coordination; autonomic indices of emotionality based on latency and amplitude along with soccer skill indices were done to realise core areas of perceptual-motor deficiencies. These evaluations were simultaneously carried out, while players were going through VMBR training, which revealed the shortcomings of majority of the players in integrating perceptual configurations involved in self-paced and externally-paced motor skill tasks. Whole-body reaction time was evaluated as measure of soccer agility skill. We observed that, the cognitively mediated VMBR training gave ample opportunity to the players to conceptualise and interpret inter-linked transitions existing between open and closed-skill activities, and this might have helped them to display excellent agility skill during performance.